2006
DOI: 10.1210/jc.2005-1880
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Loss of Heterozygosity in Imprinted, Compared with Nonimprinted, Genomic Regions in Follicular Thyroid Carcinomas and Atypical Adenomas

Abstract: Our observations suggest that IRs are more prone to genomic instability in FTCs. The fact that the ATY trended toward differential IR/NIR LOH, similar to FTC, may suggest that loss of IR might be instrumental in the adenoma-carcinoma sequence in thyroid carcinogenesis and that ATY could be an important intermediate in this pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…Overlapping values were found in some individual cases of FA and FCmi exhibiting unusually low and high levels of tpo expression respectively. This overlapping was consistent with recent data suggesting the existence of an adenoma-carcinoma sequence in which a subset of FA might predispose to malignant transformation (Vasko et al 2004, Sarquis et al 2006. The finding that tpo is significantly lower in FCwi than FCmi and higher in PCfv than PCc confirms the strong correlation between tpo expression and follicular differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Overlapping values were found in some individual cases of FA and FCmi exhibiting unusually low and high levels of tpo expression respectively. This overlapping was consistent with recent data suggesting the existence of an adenoma-carcinoma sequence in which a subset of FA might predispose to malignant transformation (Vasko et al 2004, Sarquis et al 2006. The finding that tpo is significantly lower in FCwi than FCmi and higher in PCfv than PCc confirms the strong correlation between tpo expression and follicular differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Tumour-specific LOH is found in sporadic FTC, with and without oxyphilia, at both 19p13.2 and 2q21 (Stankov et al 2004). Another study found LOH at 14q32 in sporadic FTA (22%) and FTC (43%; Sarquis et al 2006). These findings suggest that tumour suppressor susceptibility genes lie in these chromosomal regions and that genetically inherited, or somatically acquired, disruptions of these genes may predispose to FNMTC initiation and/or progression.…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that the overall LOH in thyroid tumors more frequently affects the regions that are imprinted, i.e., those with parent-specific expression of genes, as compared to non-imprinted regions [177].…”
Section: Loss Of Heterozygositymentioning
confidence: 99%